Treatment of malignant melanoma - a review of the literature - Kluz, Natalia; Klas, Jakub (Journal of Education, Health and Sport, 2021)
Melanoma is caused by genetic mutations in melanocytes, pigment-producing cells found in the skin, eye, inner ear, and soft meninges. Sun exposure, atypical nevi, previous history of melanoma, and the presence of multiple (≥40) common nevi were found to be associated with an increased risk of melanoma detection (OR: 1. 3; 95% CI: 1. 1-1. 6). Its prevalence is highest among light-skinned populations and in regions of lower latitudes. Significance of family history of melanoma and presence of congenital nevi were excluded. For localized primary melanoma, the dominant prognostic factors for survival are lesion thickness, ulceration, and lymph node involvement Understanding the pathogenesis of melanoma has been crucial in developing new therapeutic approaches. The characterization of oncogenic signaling pathways and interactions has made it possible to identify new targets for clinically effective therapies, such as pathway inhibitors and antibodies to immune checkpoints or the use of phototherapy. In this article we describe the main signaling pathways which are deregulated in melanoma. We also mention how it has become a viable and crucial strategy for melanoma therapy and then thoroughly review the safety, clinical efficacy and progress regarding PDT- promising alternative therapy and the immunotherapies of melanoma in especially advanced metastatic stage basing on published clinical data and registered clinical trials, most of which are in phase III.